Backpackers as a Community of Strangers: The Interaction Order of an Online Backpacker Notice Board - Adkins, Barbara; Grant, Eryn (Qualitative Sociology Review, 2007)
While commercial images of “backpacking” emphasise adventure, youth and sightseeing, recent ethnographies of backpackers identify other motivations and rationales that accentuate travel experiences as formative of the self and identity. This raises the question of the basis of this apparently common orientation. This paper investigates, through analysis of postings on an electronic backpacker notice board, “backpacker” as a collaboratively constructed category. We propose that the shared understandings of “backpacker” enabled by these notice boards are consistent with cultural orientations captured in notions of cosmopolitanism (Beck 2000) involving a shift to new forms of sociality across borders: a solidarity with strangers.